The making of modern intellectual property law : the British experience, 1760-1911 - Sherman, Brad (Cambridge studies in intellectual property rights., 1999)
This book is the first detailed historical account of why intellectual property law with its sub-categories of patents, copyright, designs and trade marks took the shape that it did over the course of the nineteenth century. The authors also discuss ways in which the law grants property status to intangibles.